Authentic Evaluation in the Qur'anic Hadith Learning Students of Madrasah Tsanawiyah Nahdlatul Ulama 1 Sumberasri Banyuwangi - Ahmad Izza Muttaqin; Amak Fadholi (FALASIFA : Jurnal Studi Keislaman, 2023)
This study focuses on describing the implementation of authentic evaluations in the cognitive, affective, and psychomotor domains of VII MTs NU Sumberasri students. This study uses a descriptive-qualitative approach. The subjects in this study were Al-Quran and Hadith teachers, students, and school principals. intake of research subjects or respondents using purposive sampling. The primary sources used in this study were interviews with the subject teachers of the Qur'an Hadith and students. The second primary source used by researchers is observations made in the study. Data collection instruments used include semi-structured interviews, direct observation, and documentation. The analysis technique used is qualitative data analysis, namely data reduction, data presentation, and conclusions. According to the findings of this study, the teacher evaluates the cognitive domain using written and oral tests. In the cognitive domain, the teacher conducts an assessment by observing and journaling. For the assessment of the psychomotor domain, the teacher carries out assessments with performance projects, assignments, and portfolios.